Schismatoglottideae (Araceae) of Borneo XIX — Piptospatha pileata, a remarkable new species from Kalimantan Timur, Indonesian Borneo - Wong Sin, Yeng; Boyce, P.C (BioOne Online Journals, 2012)
Piptospatha pileata, a new species of the Araceae tribe Schismatoglottideae from Kalimantan Timur province, Indonesian Borneo, is described, comparatively illustrated and delimited from P. burbidgei and P. elongata, and included in a revised key to the species of the genus.